Driving Sustainable Performance through Intellectual Capital: Empirical Evidence from Islamic Banking in Indonesia - Widia Astuty; Fajar Pasaribu; Azwansyah Habibie; Sri Rahayu (Institut Bisnis dan Informatika Kesatuan, 2025)
Islamic banking is increasingly expected to achieve not only financial performance but also environmental, social, and governance sustainability in line with the principles of Maqasid al-Shariah. However, empirical evidence examining the role of intellectual capital in promoting sustainable financial performance remains limited. Therefore, this study investigates the effect of intellectual capital, measured using the Islamic banking value-added intellectual coefficient, on sustainable financial performance in Indonesian Islamic commercial banks. A quantitative ex post facto design was employed using secondary data from nine Islamic commercial banks during 2020–2024, resulting in 36 bank-year observations. The data were analyzed using Higher-Order PLS-SEM. The findings reveal that intellectual capital positively and significantly influences sustainable financial performance. Furthermore, sustainable financial performance positively affects financial, environmental, social, and governance performance, indicating that sustainability is reflected across multiple organizational dimensions. The structural model demonstrates satisfactory explanatory power, predictive relevance, and good model fit. These findings confirm that intellectual capital is a strategic resource for strengthening sustainability-oriented performance in Islamic banking.